2021
DOI: 10.3389/fevo.2021.707708
|View full text |Cite
|
Sign up to set email alerts
|

The BAHD Gene Family in Cacao (Theobroma cacao, Malvaceae): Genome-Wide Identification and Expression Analysis

Abstract: The benzyl alcohol O-acetyl transferase, anthocyanin O-hydroxycinnamoyl transferase, N-hydroxycinnamoyl anthranilate benzoyl transferase, and deacetylvindoline 4-O-acetyltransferase (BAHD) enzymes play a critical role in regulating plant metabolites and affecting cell stability. In the present study, members of the BAHD gene family were recognized in the genome of Theobroma cacao and characterized using various bioinformatics tools. We found 27 non-redundant putative tcBAHD genes in cacao for the first time. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Then, the Conserved Domain Database of NCBI was used to identify conserved structural domains, and genes containing the structural domain of CuAO were retained. Referring to the method in the reference [ 45 ], the evolutionary tree construction and kinship analysis were performed using the maximum likelihood method in MEGA, multiplex protein sequence alignment was performed using DNAman, and gene structure and chromosomal localization were analyzed using TBtools [ 46 ]. The cis -acting elements of the promoter were predicted using the PlantCARE online website ( (accessed on 10 August 2022)) and mapped using TBtools.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the Conserved Domain Database of NCBI was used to identify conserved structural domains, and genes containing the structural domain of CuAO were retained. Referring to the method in the reference [ 45 ], the evolutionary tree construction and kinship analysis were performed using the maximum likelihood method in MEGA, multiplex protein sequence alignment was performed using DNAman, and gene structure and chromosomal localization were analyzed using TBtools [ 46 ]. The cis -acting elements of the promoter were predicted using the PlantCARE online website ( (accessed on 10 August 2022)) and mapped using TBtools.…”
Section: Methodsmentioning
confidence: 99%
“…In Clade V, the TwBAHDs function as hydroxycinnamoyl transferase, which is involved in lignin synthesis, mediating plant growth and development [38]. In Clade VI, TwBAHD21, TwBAHD92, and TwBAHD108 are orthologs of aliphatic suberin feruloyl transferase, feruloyltransferase, and deficient in cutin ferulate [39]; also in this clade, TwBAHD23, TwBAHD42, TwBAHD56, TwBAHD97, and TwBAHD98 are orthologs of alcohol acyltransferase, which is required to produce volatile esters [40]. However, in most cases, the clade members of T. mairei clearly pos-sess their own branch in phylogeny compared with the identified members from other species, which further indicated that these TwBAHDs may also be functionally different from orthologs in other species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physiological data about hormones and plant growth promotion, we further analyzed the data at the molecular level by transcriptomic analysis experiment by using two kinds of samples, 100 ppm IBA-treated buds (T) and control buds (CK). In recent times, modern biotechnological, bioinformatics tools and big-data platforms have helped understand the functions of genes and gene families up to depth ( Hoang et al, 2017 ; Abdullah et al, 2021 ; Faraji et al, 2021 ; Heidari et al, 2021 ; Manechini et al, 2021 ). In this study, RNA-seq results revealed that The IBA treatment significantly influenced DEGs regulation.…”
Section: Discussionmentioning
confidence: 99%